19 Evaluating meaningful change in disease activity as a clinical efficacy measure for clinical trials in cutaneous lupus erythematosus. (April 2019) - Chakka, Srita; Krain, Rebecca L; Ahmed, Sarah; Feng, Rui; Werth, Victoria P
Abstract : Background: To date, there are no approved treatments for cutaneous lupus erythematous (CLE), a disease known to significantly burden a patients quality of life (QoL). Clinical trials are important for the advancement of treatments for CLE and trial outcome measures should reflect clinically meaningful improvement in disease activity and its effect on QoL. Currently, trials use an efficacy measure of 50% improvement in disease activity, defined by the Cutaneous Lupus Disease Area and Severity Index (CLASI) score for activity (CLASI-A), in patients with an initial CLASI-A 10. We aim to define the degree of improvement in disease activity needed to have a meaningful impact on QoL, an important variable in the design and interpretation of future clinical trials. Methods: This study included 126 patients seen at the Autoimmune Skin Disease Clinic at the Hospital of the University of Pennsylvania who participate in a longitudinal research database. Patients with mild, moderate or severe initial CLASI-A were analyzed separately, with further stratification of patients with mild initial activity. A linear regression model was used to calculate the percent change and difference needed in CLASI-A to have an important impact on QoL, defined as a 9.38-point and a 7.37-point improvement in the Emotions and Symptoms subscales of Skindex-29, respectively. Results: In patients with an initial CLASI-A 8, an improvement of 42.1% or 7-points and an improvement of 31.0% or 5-points in disease activity is associated with a meaningful improvement in the Emotions and the Symptoms subscales, respectively. For both subscales, patients with increasingly severe initial disease required a smaller percent change in CLASI-A to predict a meaningful change in QoL (table 1 ). Conclusions: We find that using a CLASI-A 8 for trial entry allows for the inclusion of patients with milder disease for whom improvement of CLASI-A by 50% results in a meaningful impact on QoL, as determined by the Emotions and Symptoms subscales of Skindex-29. In patients with CLASI-A 8, a decrease in activity by seven and five-points is not only a clinically significant improvement but also indicates a meaningful impact on the Emotions and Symptoms subscales, respectively. For trials enrolling patients with CLASI-A 20, we recommend stratifying patients by disease severity, as a smaller percent change in activity in patients with severe disease can predict meaningful improvement in QoL. Our findings establish appropriate trial endpoints by determining clinically significant change in disease activity associated with meaningful changes in patients QoL. Funding Source(s): NIH/NIAMS 1R01AR071653 - 01A1